Kepemimpinan Kepala Madrasah Dalam Membentuk Nilai-Nilai Religius Di Madrasah Tsanawiyah Negeri 8 Banyuwangi - Najah, Safinatun; ., Subakri (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2026)
The formation of religious values in students is one of the important goals in national education and madrasah education, which is greatly influenced by the leadership of the madrasah principal. In their leadership role, madrasah principals have the responsibility to guide, mentor, and set an example in instilling religious values in the entire madrasah community. However, in reality, the religious values that madrasahs strive to instill have not been fully internalized and reflected in the daily behavior of students, especially in their daily lives outside the madrasah environment. The objectives of this study are to: 1.) Identify the leadership strategies of the madrasah principal in shaping religious values at Madrasah Tsanawiyah Negeri 8 Banyuwangi. 2.) Identify the obstacles and challenges faced by the madrasah principal in building religious values at Madrasah Tsanawiyah Negeri 8 Banyuwangi. This study uses a qualitative approach with a descriptive research type. Data collection techniques were carried out through interviews, observations, and documentation. The research subjects consisted of the Madrasah Principal and guidance counselors (BK) at Madrasah Tsanawiyah Negeri 8 Banyuwangi. Data analysis was carried out through data reduction, data presentation, and conclusion drawing. Data validity was ensured through source triangulation and technique triangulation.The field findings were as follows: 1.) The principal's leadership strategy in shaping the religious values of students through habituation and exemplary behavior. This strategy is implemented through regular religious activities and the principal setting an example of religious attitudes and behavior to the entire madrasah community. 2.) The obstacles and challenges faced by the principal in building religious values are that students are not yet fully able to internalize and apply religious values within themselves, especially when they are outside the madrasah environment, such as at home. The main challenge is the lack of support from families and the influence of social media, which significantly affects the behavior and attitudes of students in their daily lives.